2009
DOI: 10.1091/mbc.e08-07-0673
|View full text |Cite
|
Sign up to set email alerts
|

The Rho1p Exchange Factor Rgf1p Signals Upstream from the Pmk1 Mitogen-activated Protein Kinase Pathway in Fission Yeast

Abstract: The Schizosaccharomyces pombe exchange factor Rgf1p specifically regulates Rho1p during polarized growth. Rgf1p activates the ␤-glucan synthase (GS) complex containing the catalytic subunit Bgs4p and is involved in the activation of growth at the second end, a transition that requires actin reorganization. In this work, we investigated Rgf1p signaling and observed that Rgf1p acted upstream from the Pck2p-Pmk1p MAPK signaling pathway. We noted that Rgf1p and calcineurin play antagonistic roles in Cl ؊ homeostas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
66
1
28

Year Published

2009
2009
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(96 citation statements)
references
References 54 publications
1
66
1
28
Order By: Relevance
“…Indeed, we describe here that rho1-596 cells, with low Rho1 activity, showed increased basal Pmk1 phosphorylation as compared to the wild-type cells. This feature seems contradictory to previous results showing that overexpression of the constitutively active rho1G15V allele increased Pmk1 phosphorylation (García et al 2009) and that Rgf1, described as specific Rho1 GEF, also can trigger activation of the cascade (García et al 2009). However, all these observations can be explained considering that the Pmk1 pathway is activated both by hypertonic and hypotonic stresses, which are expected in gain-of-function or loss-of-function Rho1 alleles, respectively (Barba et al 2008).…”
Section: Discussioncontrasting
confidence: 96%
“…Indeed, we describe here that rho1-596 cells, with low Rho1 activity, showed increased basal Pmk1 phosphorylation as compared to the wild-type cells. This feature seems contradictory to previous results showing that overexpression of the constitutively active rho1G15V allele increased Pmk1 phosphorylation (García et al 2009) and that Rgf1, described as specific Rho1 GEF, also can trigger activation of the cascade (García et al 2009). However, all these observations can be explained considering that the Pmk1 pathway is activated both by hypertonic and hypotonic stresses, which are expected in gain-of-function or loss-of-function Rho1 alleles, respectively (Barba et al 2008).…”
Section: Discussioncontrasting
confidence: 96%
“…However, Spn1 appeared to localize normally when either Rgf1 or Rgf3 was overexpressed ( Figure 4F). In addition, the mild vegetative phenotypes of rgf1D and rgf2D mutants (Morrell-Falvey et al 2005;Mutoh et al 2005;García et al 2006García et al , 2009bour unpublished data) suggest that septin function is not perturbed by a lack of Rgf1 or Rgf2, and septins also appeared to localize normally in an rgf3-s44 mutant strain ( Figure 3B). …”
Section: Resultsmentioning
confidence: 90%
“…These synthases are regulated by the Rho GTPases Rho1 and Rho2 and the protein kinase C isoforms Pck1 and Pck2 (Arellano et al 1996(Arellano et al , 1997Nakano et al 1997;Hirata et al 1998;Calonge et al 2000;Sayers et al 2000;Ma et al 2006;Barba et al 2008;García et al 2009b). The Rho GTPases themselves appear to be regulated by both GTPase-activating proteins (GAPs) and guanine-nucleotide-exchange factors (GEFs) (Nakano et al 2001;Calonge et al 2003;Iwaki et al 2003;Tajadura et al 2004;Morrell-Falvey et al 2005;Mutoh et al 2005;García et al 2006García et al , 2009a.…”
mentioning
confidence: 99%
“…Sporulation phenotype of wild type (YS260), bgs2D (MS228), rgf2D (PG9), and rgf2Dbgs2D (NG188) homothallic haploid strains highly conserved region of the DH domain and is where many mutations that decrease nucleotide exchange activity map (Liu et al 1998;Soisson et al 1998). We have previously shown that a similar mutation in Rgf1p (rgf1-PTTRD mutant) produces a loss-of-function phenotype (García et al 2006a(García et al , 2009). As expected, overexpression of the rgf2-PTTRD mutant in a pREP3X vector produced viable cells and no multiseptated phenotype was seen, even at very long times of derepresion in the absence of thiamine ( Figure 4A).…”
Section: Rgf2p Contains a Putative Dbl Homology Domain (Dh)mentioning
confidence: 99%
“…Thus, it is probable that Rgf3p stimulates Rho1p-mediated activation of a type of GS activity that is crucial for proper septum function (Tajaduraet al 2004). Rgf1p is not essential for viability, but it does play an important role in regulating the growth pattern of fission yeast cells and signals upstream from the Pmk1 mitogenactivated protein kinase pathway (García et al 2006a(García et al , 2009. Rgf1p localizes to the cell tips in interphase cells and to the division septum in mitotic cells, and it activates the b-GS complex containing the catalytic subunit Bgs4p (Morrell-Falvey et al 2005;Mutoh et al 2005;García et al 2006a).…”
mentioning
confidence: 99%